Small mammals from Kuala Atok-Taman Negara Pahang, Malaysia - Roberta Chaya Tawie Tingga,; Anwarali, F.A; Mohd Ridwan, A.R; Senawi, J; Abdullah, M.T (Universiti Kebangsaan Malaysia, 2012)
A faunal survey aimed to document small mammals was conducted at Nature Study Centre of Kuala Atok, Taman Negara Pahang from 16th to 23rd May 2008. This survey was part of the Biodiversity Inventory Programme that was organised by the Department of Wildlife and National Parks (DWNP). On average, ten mist nets, two four-bank harp traps, 100 cage traps and 40 Sherman traps were set for six trapping nights. A total of 79 individuals from three orders, seven families and 23 species were caught in this study. Of the 23 species, three were frugivorous bats, 15 were insectivorous bats, four were rodents and one was treeshrew. Our sampling site was bounded by Pahang River and mainly covered with lowland secondary forest. This is evidence by the highest abundance of Long-tailed Giant Rat (Leopoldamys sabanus) for non-volant small mammals, and Fawn Roundleaf Bat (Hipposideros cervinus) for volant small mammals that are adapted to disturbed habitat. The increasing species cumulative curve for Chiropteran indicates that there may be more species yet to be recorded from this study site compared to rodents and treeshrews. Preliminary analysis on the species similarity between our study site to other survey reports in Peninsular Malaysia, positioned Kuala Atok with Krau Wildlife Reserve and Bukit Fraser Forest Reserve that are located adjacent to our study site. This similarity further indicate the importance of future survey in Kuala Atok especially for Chiropterans to properly document the species diversity in this site that may be as rich as other well studied area e.g. Krau Wildlife Reserve.